ANALISIS PENDAPATAN USAHATANI JAGUNG PAKAN DI DESA MAGALAU HULU KABUPATEN KOTABARU - Refiana, Fenny; Fitriadi, Subhan; Triatmoko, Eddy (Chlorophyl, 2024)
The purpose of this research is to know technical aspects of feed corn farming the revenue,the eksplicit cost and the income farmer.This research was conducted in April until Juni 2024 in Magalau hulu village. The purposive sampling methode used was by observing 22 farmers in village Magalau hulu who planted feed corn plant. The Average result of the revenue is Rp. 17.382.400,/farmer, The average eksplicit cost is Rp. 8.538.281 /farmer, and Average income Rp. 8.844.119 /farmer.We believe that it has good prospect and revenue, of the average income ,tecnicall,economically